KwaZakele: the politics of transition in South Africa: an Eastern Cape case study - Cherry, Janet Mary (Rhodes University, Faculty of Humanities, Department of Political Studies, 2001)
This thesis examines the transition to democracy in South Africa through the use of case study methodology. The nature of political participation and the form of democracy to emerge at the end of the transition process are the central subjects of inquiry. They are examined through an in-depth study of the African community of Kwazakele, a township in the Nelson Mandela metropolitan area in the Eastern Cape province of South Africa. The study covers the period from 1993 to 2000, and uses as a primary data source five surveys conducted among residents of Kwazakele during that period. The emphasis of the study lies on the experience of political participation of 'ordinary people' "“ in particular, the African urban working-class in South Africa who make up the core support base for the governing African National Congress. The primary findings of the thesis are as follows: * Representative democracy has been successfully consolidated in the community under study. * Levels of political participation by urban Africans in the Eastern Cape are consistently high, both in formal political institutions (primarily elections) and in institutions of civil society. * As politics has normalised at the end of the transition period, forms of direct democratic participation have declined. * Despite the structural constraints on development, there is still potential for a high level of participation by citizens in effecting change at local level. * Drawing on the experience of ordinary people in structures of direct democracy, this level of participation can result in a deeper and stronger form of democracy than exists in many established representative democracies.
Keywords: South Africa -- Transition to democracy; Democracy -- South Africa -- Eastern Cape; Eastern Cape (South Africa) -- Politics and government; Port Elizabeth region (South Africa) -- Political aspects